Local Wisdom-Based Village Potential of Talekoi and Danau Bambure Village: IKN Buffer Areas - Luluk Tri Harinie; Muhamad Romadoni; Meylinda Sukmani; John Budiman Bancin (Jurnal Ilmu Sosial dan Humaniora, 2024)
The results of available natural resources became a village potential that deserved to be developed as an independent effort for the village's well-being. This research aimed to reveal the potential of the local wisdom-based village in Talekoi and Danau Bambure Village as an effort to strengthen the IKN buffer areas. Qualitative research with phenomenological designs was the analytical tool. Research informants comprised two village chiefs, two public figures, and two youth figures. Data collection methods included partitional observations, in-depth interviews, and document study. The data analysis used was an interactive model of Miles and Huberman. The result of the research showed that the stink bean farm and salted fish processing from Talekoi Village was an economic activity for promising village potential. Furthermore, lake tourism and clean water in Danau Bambure Village became the leading potential in utilizing local wisdom-based village potential and preparing the village's well-being to strengthen the IKN buffer areas.